The mediating role of instrumental activities of daily living in the relation between cognitive function and life satisfaction among Malaysian community-dwelling older adults: do gender and age matter? - Foong, Hui Foh; Ibrahim, Rahimah; Hamid, Tengku Aizan; Bagat, Mohamad Fazdillah (Springer, 2023)
Cognitive function (CF) is a resource for instrumental activities of daily living (IADL) and life satisfaction (LS) in old age. Besides, IADL also contributes to LS in old age. However, the mediating role of IADL in the relation between CF and LS, especially from a longitudinal sample, is lacking. Therefore, the main aim of this study was to examine the mediating role of IADL in the relationship between CF and LS using two-wave sample data. This study also determined if the mediation model differed by gender and age. Data from two waves of the “Neuroprotective Model for Healthy Longevity among Malaysian Older Adults” study were extracted. The data collection was conducted in four states of Peninsula Malaysia. The first wave of data collection was completed in February 2013, while the second wave was conducted three years after the first wave. The participants were interviewed by trained enumerators using a structured questionnaire. The mediating role of IADL in the relationship between CF and LS was examined using PROCESS macro (model 4) for SPSS. Multigroup modelling using AMOS was used to explore the moderating roles of gender and age on the mediational model. Among the 2,315 respondents at T1, 1,294 were included in the T2 survey. IADL was found to partially mediate the relationship between CF and LS (indirect effect = 0.004, LLCI = 0.002, ULCI = 0.005). In addition, the relationship between CF and IADL was more prominent in men (β = 0.073, P < 0.001) than women (β = 0.047, P < 0.001) (t = 2.456, P = 0.014); the relationships between CF IADL was more pronounced in older respondents (β = 0.075, P < 0.001) than younger respondents (β = 0.038, P < 0.001) (t = 3.342, P = 0.001); and the relationships between and CF LS was more pronounced in older respondents (β = 0.070, P < 0.001) than younger respondents (β = 0.016, P = 0.068) (t = 3.989, P < 0.001). The developed conceptual model may facilitate an understanding of how CF, IADL, gender, and age interact to promote LS in later life. This model is helpful in the formulation of strategies to improve life satisfaction.